2017
DOI: 10.1016/j.jpainsymman.2016.12.131
|View full text |Cite
|
Sign up to set email alerts
|

Association of POST Form Use with Quality End-of-Life Care Metrics in Cancer Patients: Update from the West Virginia Registry (FR440B)

Abstract: Objectives Discuss Advance Care Planning approaches used by cardiovascular disease decedents in a nationally representative sample. Identify significant symptoms experienced in the last year of life for decedents of cardiovascular disease. Describe the association of symptom burden with the proclivity to engage in advance care planning in individuals dying of cardiovascular disease. Original Research Background. The unpredictable disease trajectory for persons dying from cardiovascular disease (CVD) may make p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…33 Pedraza and colleagues (n = 2159) found the odds of dying outside the hospital were more than 2 times greater for patients with POLSTs than patients with ADs (OR = 2.3, P < .001). 44…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Pedraza and colleagues (n = 2159) found the odds of dying outside the hospital were more than 2 times greater for patients with POLSTs than patients with ADs (OR = 2.3, P < .001). 44…”
Section: Resultsmentioning
confidence: 99%
“…33 Pedraza and colleagues (n ¼ 2159) found the odds of dying outside the hospital were more than 2 times greater for patients with POLSTs than patients with ADs (OR ¼ 2.3, P < .001). 44 Of the 11 studies that assessed hospice use, 9 studies found significant associations with EOL discussions (ORs ranging 1.79-6.88). 23,32,35,38,39,42,47,51 Findings were strongest among studies that defined discussions based on EOL, GOC, and treatment preference conversations.…”
Section: Summary Of Findingsmentioning
confidence: 99%